High-entropy stannate fiber with rare earth pyrochlore structure and preparation method of stannate fiber

By preparing high-entropy rare earth calcinite structure stannate fibers, the problem of structural failure during the preparation of high-entropy calcinite oxide fibers and high-temperature sintering is solved, and fiber materials with high-temperature tolerance and corrosion resistance are realized, and their application prospects in the fields of catalysis and high-temperature are expanded.

CN119900109APending Publication Date: 2025-04-29SHIJIAZHUANG TIEDAO UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510275532.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-10
Publication Date
2025-04-29

AI Technical Summary

Technical Problem

It is difficult to successfully prepare high-entropy calcinedite oxide fibers in the prior art, and the fibers are prone to structural damage and performance degradation when sintered at high temperatures.

Method used

High-entropy rare earth calcinite structure stannate fibers and their preparation methods are used to mix four rare earth nitrates with anhydrous tin chloride in an ethanol solution, add spinning additives and prepare fibers through electrospinning process, and calcinate at a high temperature of 800~1100°C to form high-entropy calcinite structure stannate fibers.

Benefits of technology

A uniform and good-shaped high-entropy calcinite structure stannate fiber has been successfully prepared, which has high temperature resistance, corrosion resistance and lightweight and high strength, and is suitable for applications in catalyst support and high temperature fields.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FT_1
    Figure FT_1
  • Figure FT_2
    Figure FT_2
  • Figure FT_3
    Figure FT_3
Patent Text Reader

Abstract

The invention discloses a high-entropy pyrochlore oxide fiber and a preparation method thereof.The preparation method comprises the following steps that 1, four rare earth nitrates are mixed and dissolved in an ethanol solution to obtain a solution A, anhydrous tin chloride is added into an acid solution to obtain a solution B, then the solution A and the solution B are mixed, a spinning auxiliary is added, the mixture is fully stirred and dissolved, and a spinning solution A is obtained; and finally obtaining a spinning precursor solution. 2, performing an electrostatic spinning process on the spinning precursor solution to obtain a high-entropy rare earth precursor fiber; and 3, calcining the high-entropy rare earth precursor fiber to obtain the stannate fiber with the high-entropy rare earth pyrochlore structure. The method is characterized in that a high entropy strategy is provided, and the stability of pyrochlore oxide is improved; the electrostatic spinning process is optimized, and the morphology uniformity problem of fiber preparation is solved; high-temperature calcination parameters are optimized, and the crystallinity and high-temperature resistance of the fiber are improved. Meanwhile, the high-entropy pyrochlore oxide fiber provided by the invention has designability and operability, the preparation process is simple, and the high-entropy pyrochlore oxide fiber plays an important role in the aspects of high-performance composite materials, catalyst carriers and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to a high-entropy rare earth pyrochlore structure stannate fiber and a preparation method thereof, belonging to the technical field of high-entropy ceramics and fiber materials. Background Art

[0002] Although many oxides have good chemical stability and corrosion resistance at high temperatures, their limitations in thermal stability, mechanical properties, electrical conductivity, etc. also restrict their high-temperature applications to a certain extent. In order to overcome these limitations, it is usually necessary to develop new high-temperature materials or improve the performance of existing materials. Pyrochlore oxide (A2B2O7) has attracted extensive attention and research due to its unique crystal structure and multifunctional properties. The pyrochlore structure is derived from the fluorite structure and has a high degree of symmetry and stability, which enables it to maintain crystal integrity under high temperature and harsh environmental conditions.

[0003] However, the current research on pyrochlore oxides mainly focuses on particle morphology, which is closely related to the advantages brought by particle morphology. Granular materials have a relatively large surface area, providing more active sites. Granular pyrochlore materials maintain good structural integrity and physicochemical properties under high temperature conditions, making them suitable for high-temperature applications. The particle size and morphology of granular pyrochlore materials can be controlled by adjusting the synthesis parameters (such as temperature, time and doping elements), which can optimize their performance in different applications.

[0004] In addition to the commonly studied particulate pyrochlore compounds, a unique morphology of pyrochlore composite oxides has been developed. By regulating the morphology of the composites, their photocatalytic performance was significantly improved. This shows that improving the morphology of the compound can have a significant impact on its material properties. The particulate morphology of pyrochlore oxides has achieved significant progress in various applications, while the study of fiber morphology is still in its infancy. Existing studies have shown that fiber morphology can provide a higher specific surface area, which is beneficial for improving catalytic and conductive properties. Therefore, it is a feasible method to prepare pyrochlore oxides with fiber morphology for catalytic applications.

[0005] Pyrochlore oxides generally have high melting points and excellent thermal stability, however, this also poses challenges to the fiber molding and sintering processes. Achieving structural integrity at high temperatures is critical to maintaining the crystalline structure. During fiber manufacturing, high-temperature sintering is usually accompanied by significant volume shrinkage, which may cause fiber cracking or morphological deformation, thereby affecting the fiber's specific surface area and functional performance. Therefore, how to solve the sintering challenges of these fiber materials is a key issue.

[0006] High entropy oxides (HEOs) are a new class of materials composed of four or more main elements in equimolar or nearly equimolar ratios. Since Rost, Maria and Curtarolo first reported rock salt structured high entropy oxides in 2015, these materials have attracted great attention from researchers as an emerging field, making high entropy ceramics show excellent application potential in many fields. The strategy of making materials high entropy can improve the structural stability of pyrochlore compounds and alleviate the adverse effects during high-temperature applications. However, the synthesis of high entropy compounds requires higher sintering temperatures, which may cause fiber fracture. However, existing technologies cannot achieve the successful preparation of high entropy pyrochlore oxide fibers. Based on this, we need to develop new processes to obtain high entropy pyrochlore oxide fibers. Technical Solution

[0007] Based on the above technical problems, the present invention proposes a high-entropy rare earth pyrochlore structure stannate fiber and a preparation method thereof. On the one hand, it can solve the problems of high-temperature application of oxide materials; on the other hand, it can solve the problems of structural destruction of fiber materials at high temperatures, resulting in performance degradation. The uniform and good high-entropy pyrochlore oxide fiber prepared by this patent can be used as a loading matrix for catalysts in use, and can also promote the application of high-entropy fiber materials in high-temperature fields.

[0008] To achieve the above objectives, the present invention proposes a high-entropy rare earth pyrochlore structure stannate fiber and a preparation method thereof. The specific technical scheme is as follows: A high-entropy rare earth pyrochlore structure stannate fiber, characterized in that it includes a high-entropy rare earth pyrochlore structure stannate fiber, whose chemical expression is A2Sn2O7, and the A position in the high-entropy rare earth pyrochlore structure stannate fiber is composed of four rare earth elements.

[0009] Furthermore, the four rare earth elements at the A position of the high-entropy rare earth pyrochlore structure stannate fiber are lanthanum, neodymium, samarium and gadolinium, the rare earth elements at the A position are introduced by lanthanum nitrate hexahydrate, neodymium nitrate pentahydrate, samarium nitrate hexahydrate and gadolinium nitrate hexahydrate, and the tin element at the B position is introduced by anhydrous tin chloride.

[0010] The present invention also provides a method for preparing high-entropy rare earth pyrochlore structure stannate fiber, which is characterized by comprising the following steps: S1: four rare earth nitrates are mixed and dissolved in an ethanol solution to obtain solution A, anhydrous tin chloride is added to an acidic solution to obtain solution B, and then solutions A and B are mixed and a spinning aid is added to fully stir and dissolve, finally obtaining a spinning precursor solution; S2: obtaining high entropy rare earth precursor fibers by electrospinning the spinning precursor solution; S3: calcining the high-entropy rare earth precursor fiber to obtain high-entropy rare earth pyrochlore structure stannate fiber.

[0011] Furthermore, in step S1, the four rare earth nitrates are lanthanum nitrate hexahydrate, neodymium nitrate pentahydrate, samarium nitrate hexahydrate and gadolinium nitrate hexahydrate, and their purity is greater than 99wt%, and the molar ratio of lanthanum nitrate hexahydrate, neodymium nitrate pentahydrate, samarium nitrate hexahydrate and gadolinium nitrate hexahydrate is 1:1:1:1, and the proportion of the four rare earth nitrates in the ethanol solution is 2-10wt%.

[0012] Furthermore, in step S1, the purity of the anhydrous tin chloride is greater than 99wt%, the acidic solution is one of dilute acetic acid and dilute hydrochloric acid, the concentrations of the dilute acetic acid and the dilute hydrochloric acid are both 1-2mol / L, and the proportion of the anhydrous tin chloride in the acidic solution is 5-15wt%.

[0013] Furthermore, in step S1, the spinning aid is polyvinyl pyrrolidone (PVP), the stirring is performed by a mechanical stirring method, the stirring rate is 50-200 rpm / min, and the stirring time is 2-10 hours.

[0014] Furthermore, in step S2, the spinning parameters of the electrospinning process are: positive electrode 15~30kv, negative electrode -10~0kv, drum speed 50~150rpm, receiving distance 5~20cm, ambient temperature 20~50℃, and ambient humidity 25~50%.

[0015] Furthermore, in step S3, the calcination treatment temperature is 800-1100° C., the heating rate is 1-5° C. / min, and the holding time is 2-10 h.

[0016] Furthermore, in step S3, according to the best example of this patent, the calcination treatment temperature is 1000°C, the heating rate is 2°C / min, and the holding time is 4h.

[0017] Based on the above technical solution, the present invention has at least the following beneficial effects: (1) The method used in the present invention to prepare the electrospinning precursor solution, i.e., the method of inhibiting the hydrolysis of anhydrous tin tetrachloride solution by hydrochloric acid, does not produce obvious solid precipitation, and the solution is colorless and uniform, which is conducive to the stability of the electrospinning process; (2) The method used in the present invention to prepare the nanofiber spinning mat is an electrospinning method, which is completed using an electrospinning machine. The process is simple and the equipment is easy to operate. It can prepare uniform nanofibers with good morphology and peel off a complete fiber mat on the release paper; (3) As a new type of material, the high-entropy rare earth pyrochlore structured stannate fiber of the present invention has the characteristics of high temperature tolerance, corrosion resistance, light weight and high strength, which makes it have significant application prospects in the fields of construction, aerospace, automobile, marine engineering, environmental protection and composite materials. With the further development of materials science, high-entropy pyrochlore fibers may find new applications in more high-end technology fields in the future and promote the development of related industries. DETAILED DESCRIPTION

[0018] In order to facilitate the understanding of the present invention, the present invention will be described more comprehensively and meticulously below in conjunction with the accompanying drawings and preferred embodiments of the present invention, but the protection scope of the present invention is not limited to the following specific embodiments.

[0019] Unless otherwise defined, all the professional terms used below have the same meanings as those generally understood by those skilled in the art. The professional terms used herein are only for the purpose of describing specific embodiments and are not intended to limit the scope of protection of the present invention. Example 1

[0020] S1: Four rare earth nitrates were mixed and dissolved in an ethanol solution at a molar ratio of 1:1:1:1 to obtain a solution A with a nitrate mass fraction of 3.5%, 94 μl of anhydrous tin chloride was added to a 1 mol / L dilute acetic acid solution to obtain a solution B with an anhydrous tin chloride content of 6.25%, and then the two solutions A and B were mixed and a polyvinylpyrrolidone spinning aid was added and stirred at 100 rpm / min for 5 h until completely dissolved, and finally a spinning precursor solution was obtained; S2: The spinning precursor solution is subjected to an electrospinning process to obtain a high entropy rare earth precursor fiber felt, wherein the spinning machine parameters are: positive electrode voltage +20kv, negative electrode voltage 0kv, drum speed 100rpm / min, receiving distance 10cm, ambient temperature 30°C, and ambient humidity 25%; S3: Remove the release paper, peel off the electrospun fiber felt, and calcine the precursor fiber felt to obtain high-entropy rare earth pyrochlore structure stannate nanofibers. The calcination temperature is 800° C., the heating rate is 5° C. / min, and the insulation time is 2 h.

[0021] The spinning precursor solution prepared in this experiment has a pungent smell and is green and transparent overall. The composition of the solution does not have a significant effect on the electrospinning process. After spinning, a relatively complete fiber mat can be peeled off from the release paper. After calcination, the fiber mat is fully debonded, the volume is significantly reduced, and the texture is brittle. The results of the XRD test on the sample are as follows Figure 1 As shown, a high-entropy pyrochlore phase was formed. Example 2

[0022] S1: Four rare earth nitrates were mixed and dissolved in an ethanol solution at a molar ratio of 1:1:1:1 to obtain a solution A with a nitrate mass fraction of 3.5%, 94 μl of anhydrous tin chloride was added to a 1 mol / L dilute hydrochloric acid solution to obtain a solution B with an anhydrous tin chloride content of 6.25%, and then the two solutions A and B were mixed and a polyvinylpyrrolidone spinning aid was added and stirred at 100 rpm / min for 6 h until completely dissolved, and finally a spinning precursor solution was obtained; S2: The spinning precursor solution is subjected to an electrospinning process to obtain a high entropy rare earth precursor fiber felt, wherein the spinning machine parameters are: positive electrode voltage +20 kV, negative electrode voltage -2 kV, drum speed 100 rpm / min, receiving distance 10 cm, ambient temperature 31° C., and ambient humidity 26%; S3: remove the release paper, peel off the electrospun fiber felt, and calcine the precursor fiber felt to obtain high-entropy rare earth pyrochlore structure stannate nanofibers. The calcination temperature is 800° C., the heating rate is 5° C. / min, and the holding time is 2 h.

[0023] The precursor solution prepared in this experiment is colorless, transparent and has no pungent odor, and the electrospinning process is more stable. After spinning, a relatively complete fiber mat can be peeled off from the release paper. The fiber mat is colorless, and its volume is significantly reduced after calcination, and its texture is brittle. The results of the XRD test on the sample are as follows Figure 2 As shown, a high-entropy pyrochlore phase was formed after calcination. Example 3

[0024] S1: Four rare earth nitrates were mixed and dissolved in an ethanol solution at a molar ratio of 1:1:1:1 to obtain a solution A with a nitrate mass fraction of 3.5%, 94 μl of anhydrous tin chloride was added to a 1 mol / L dilute hydrochloric acid solution to obtain a solution B with an anhydrous tin chloride content of 6.5%, and then the two solutions A and B were mixed and a spinning aid was added to the polyvinyl pyrrolidone spinning aid, and the spinning aid was fully stirred at 150 rpm / min for 6 hours until it was completely dissolved, and finally a spinning precursor solution was obtained; S2: The spinning precursor solution is subjected to an electrospinning process to obtain a high entropy rare earth precursor fiber felt, wherein the spinning machine parameters are: positive electrode voltage +21 kv, negative electrode voltage -2 kv, drum speed 150 rpm / min, receiving distance 11 cm, ambient temperature 32° C., and ambient humidity 27%; S3: Remove the release paper, peel off the electrospun fiber felt, and calcine the precursor fiber felt to obtain high-entropy rare earth pyrochlore structure stannate nanofibers. The calcination temperature is 900° C., the heating rate is 5° C. / min, and the holding time is 2 h.

[0025] The XRD test results of the samples obtained in this example are as follows: Figure 3As shown, a high entropy pyrochlore phase was obtained and the crystallinity of the pyrochlore phase increased. Example 4

[0026] S1: Four rare earth nitrates were mixed and dissolved in an ethanol solution at a molar ratio of 1:1:1:1 to obtain a solution A with a nitrate mass fraction of 3.5%, 94 μl of anhydrous tin chloride was added to a 1 mol / L dilute hydrochloric acid solution to obtain a solution B with an anhydrous tin chloride content of 7%, and then the two solutions A and B were mixed and a polyvinylpyrrolidone spinning aid was added and stirred at 100 rpm / min for 6 h to fully stir and dissolve, and finally a spinning precursor solution was obtained; S2: The spinning precursor solution is subjected to an electrospinning process to obtain a high entropy rare earth precursor fiber felt, wherein the spinning machine parameters are: positive electrode voltage +21 kv, negative electrode voltage -2 kv, drum speed 100 rpm / min, receiving distance 12 cm, ambient temperature 33° C., and ambient humidity 28%; S3: Remove the release paper, peel off the electrospun fiber felt, and calcine the precursor fiber felt to obtain high-entropy rare earth pyrochlore structure stannate nanofibers. The calcination temperature is 1000° C., the heating rate is 2° C. / min, and the insulation time is 4 h.

[0027] The XRD results obtained are as follows Figure 4 As shown, compared with Examples 2 and 3, the diffraction peak of the tin dioxide phase corresponding to the diffraction angle 2θ≈28° is reduced. The intensity of the diffraction peak at 29-29.5° increases, and the crystallinity of the high-entropy pyrochlore phase increases. Figure 5 The morphology and element distribution of the fiber prepared in the example under a high-power lens are shown, indicating that the fiber is formed and the element distribution is uniform without obvious segregation.

[0028] Comparative Example 1: S1: Four rare earth nitrates were mixed and dissolved in an ethanol solution at a molar ratio of 1:1:1:1 to obtain a solution A with a nitrate mass fraction of 3.5%, 100 μl of anhydrous tin chloride was added to the ethanol solution to obtain a solution B with an anhydrous tin chloride content of 6.25%, and then the two solutions A and B were mixed and a polyvinylpyrrolidone spinning aid was added and stirred at 100 rpm / min for 5 h to fully stir and dissolve, and finally a spinning precursor solution was obtained; S2: The spinning precursor solution is subjected to an electrospinning process to obtain a high entropy rare earth precursor fiber felt, wherein the spinning machine parameters are: positive electrode voltage +20 kV, negative electrode voltage -2 kV, drum speed 100 rpm / min, ambient temperature 30°C, and ambient humidity 25%; S3: Remove the release paper, peel off the electrospun fiber felt, and calcine the precursor fiber felt to obtain high-entropy rare earth pyrochlore structure stannate nanofibers. The calcination temperature is 700° C., the heating rate is 5° C. / min, and the calcination time is 2 h.

[0029] The prepared precursor solution is yellow and turbid, which is caused by the stirring and dispersion of the hydrolysis product of anhydrous SnCl4. The spinning precursor solution prepared by this method makes the spinning process unstable, and the droplet blocks the needle mouth seriously, generating pressure and causing the spinning machine to alarm. The peeled fiber felt is broken, resulting in the nanofibers obtained after calcination being of different sizes, mostly debris. XRD test characterization is performed on it, and the results are as follows Figure 6 As shown, a more obvious diffraction peak was found at a diffraction angle of about 2θ≈28°, indicating the presence of SnO2 impurity phase.

[0030] Comparative Example 2: S1: 0.35 g of lanthanum nitrate was dissolved in an ethanol solution to obtain a solution A with a nitrate mass fraction of 3.5%, 100 μl of anhydrous tin chloride was added to the ethanol solution to obtain a solution B with an anhydrous tin chloride content of 6.25%, and then the two solutions A and B were mixed and a polyvinylpyrrolidone spinning aid was added and stirred at 100 rpm / min for 5 hours to fully stir and dissolve, and finally a spinning precursor solution was obtained; S2: The spinning precursor solution is subjected to an electrospinning process to obtain a high entropy rare earth precursor fiber felt, wherein the spinning machine parameters are: positive electrode voltage +15 kV, negative electrode voltage -2 kV, drum speed 100 rpm / min, ambient temperature 30°C, and ambient humidity 25%; S3: Remove the release paper, peel off the electrospun fiber felt and dry it at 60°C for 12 hours. The precursor fiber felt is calcined at 800°C, at a heating rate of 2°C / min, and for 2 hours.

[0031] The calcined sample has no fiber morphology and is in powder form.

[0032] The above are only a few embodiments of the present application and do not constitute any form of limitation to the present application. Although the present application is disclosed as above with preferred embodiments, it is not intended to limit the present application. Any technician who makes slight changes or modifications using the technical contents disclosed above without departing from the scope of the technical solution of the present application is equivalent to an equivalent implementation case and is within the technical scope.

[0033] Description of the attached figures / tables: Figure 1 : XRD test results of the fiber sample in Example 1.

[0034] Figure 2 : XRD test results of the fiber sample in Example 2.

[0035] Figure 3 : XRD test results of the fiber sample in Example 3.

[0036] Figure 4 : XRD test results of the fiber sample in Example 4.

[0037] Figure 5 : HRTEM morphology and elemental characterization of the fiber sample in the embodiment.

[0038] Figure 6 : XRD test results of the fiber sample in Comparative Example 1.

Claims

1. A high entropy rare earth pyrochlore structure stannate fiber, characterized in that: The invention comprises high-entropy rare earth pyrochlore structure stannate fiber, the chemical expression of which is A2Sn2O7, and the A position of the high-entropy rare earth pyrochlore structure stannate fiber is composed of four rare earth elements.

2. The high entropy rare earth pyrochlore structure stannate fiber according to claim 1, characterized in that: The four rare earth elements at the A position are lanthanum, neodymium, samarium and gadolinium. The rare earth elements at the A position are introduced by lanthanum nitrate hexahydrate, neodymium nitrate pentahydrate, samarium nitrate hexahydrate and gadolinium nitrate hexahydrate. The tin element at the B position is introduced by anhydrous tin chloride.

3. A method for preparing high-entropy rare earth pyrochlore structure stannate fiber as claimed in claim 1, characterized in that: The steps include: S1: four rare earth nitrates are mixed and dissolved in an ethanol solution to obtain solution A, anhydrous tin chloride is added to an acidic solution to obtain solution B, and then solutions A and B are mixed and a spinning aid is added to fully stir and dissolve, finally obtaining a spinning precursor solution; S2: obtaining high entropy rare earth precursor fibers by electrospinning the spinning precursor solution; S3: calcining the high entropy rare earth precursor fiber to obtain high entropy rare earth pyrochlore structure stannate fiber.

4. The method for preparing high-entropy rare earth pyrochlore structure stannate fiber according to claim 3, characterized in that: In S1, the four rare earth nitrates are lanthanum nitrate hexahydrate, neodymium nitrate pentahydrate, samarium nitrate hexahydrate and gadolinium nitrate hexahydrate, and their purity is greater than 99wt%, and the molar ratio of lanthanum nitrate hexahydrate, neodymium nitrate pentahydrate, samarium nitrate hexahydrate and gadolinium nitrate hexahydrate is 1:1:1:1, and the proportion of the four rare earth nitrates in the ethanol solution is 2-10wt%.

5. The method for preparing high-entropy rare earth pyrochlore structure stannate fiber according to claim 3, characterized in that: In S1, the purity of the anhydrous tin chloride is greater than 99wt%, the acidic solution is one of dilute acetic acid and dilute hydrochloric acid, both with a concentration of 1-2mol / L, and the proportion of the anhydrous tin chloride in the acidic solution is 5-15wt%.

6. The method for preparing high-entropy rare earth pyrochlore structure stannate fiber according to claim 3, characterized in that: In S1, the spinning aid is polyvinylpyrrolidone (PVP), the stirring is performed by a mechanical stirring method, the stirring rate is 50-200 rpm / min, and the stirring time is 2-10 h.

7. The method for preparing high-entropy rare earth pyrochlore structure stannate fiber according to claim 3, characterized in that: In S2, the spinning parameters of the electrospinning process are: positive electrode 15~30kv, negative electrode -10~0kv, drum speed 50~150rpm, receiving distance 5~20cm, ambient temperature 20~50℃, and ambient humidity 25~50%.

8. The method for preparing high-entropy rare earth pyrochlore structure stannate fiber according to claim 3, characterized in that: In S3, the calcination treatment temperature is 800-1100°C, the heating rate is 1-5°C / min, and the holding time is 2-10h.

9. According to claim 8, it is characterized in that: In S3, the calcination treatment temperature is 1000°C, the heating rate is 2°C / min, and the holding time is 4h.